2021
DOI: 10.1177/2192568220988276
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes After Complex Adult Spinal Deformity Surgery: 5-Year Results of the Scoli-Risk-1 Study

Abstract: Study Design: Prospective cohort. Objective: To prospectively evaluate PROs up to 5-years after complex ASD surgery. Methods: The Scoli-RISK-1 study enrolled 272 ASD patients undergoing surgery from 15 centers. Inclusion criteria was Cobb angle of >80°, corrective osteotomy for congenital or revision deformity, and/or 3-column osteotomy. The following PROs were measured prospectively at intervals up to 5-years postoperative: ODI, SF36-PCS/MCS, SRS-22, NRS back/leg. Among patients with 5-year follow-up, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This article also stratified the shift in ODI based on preoperative ODI deciles, which is a useful counseling tool for shared decision-making. Similar findings were identified in the 5-year outcomes reported by the Scoli-RISK-1 Study Group 37 . This study was limited by a 5-year follow-up rate of 28%, but identified a significant improvement in patient-reported outcomes, with 62% of patients having a clinically meaningful improvement in the ODI score.…”
Section: Adult Spinal Deformitysupporting
confidence: 87%
“…This article also stratified the shift in ODI based on preoperative ODI deciles, which is a useful counseling tool for shared decision-making. Similar findings were identified in the 5-year outcomes reported by the Scoli-RISK-1 Study Group 37 . This study was limited by a 5-year follow-up rate of 28%, but identified a significant improvement in patient-reported outcomes, with 62% of patients having a clinically meaningful improvement in the ODI score.…”
Section: Adult Spinal Deformitysupporting
confidence: 87%
“…[ 51 ] Scoli-RISK-1 study revealed that patient-reported outcomes were better at 5 years postoperative in ODI, Short Form 36, Physical and Mental Component Score, SRS-22r score, and Numerical Rating Scale for back/leg pain. [ 52 ]…”
Section: Discussionmentioning
confidence: 99%
“…Spinal fusion to correct ASD has been shown to improve health-related quality of life 5–7. However, the effects of long-segment fusion on patient balance and postural control is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal fusion to correct ASD has been shown to improve health-related quality of life. [5][6][7] However, the effects of long-segment fusion on patient balance and postural control is poorly understood. It is well understood that postural instability leads to increased incidence of falls, and preventing a fall requires quick corrections of the COG and an optimal position in the patient's COE.…”
Section: Discussionmentioning
confidence: 99%